Alloying effect of titanium on WCp/Al composite fabricated by coincident wire-powder laser deposition. (5th March 2016) - Li, Fuquan; Gao, Zhenzeng; Zhang, Yang; Chen, Yanbin
Abstract: Combined wire and powder deposition by laser (WPDL) has proven to be a promising method for the fabrication of Metal Matrix Composite (MMCs) materials. In this paper, aluminum matrix composites were fabricated by the WPDL method, where WC powder was fed from a coaxial nozzle, while aluminum wire was fed from a lateral nozzle into a laser generated melt pool. It was found that the WC particles had dissolved into the aluminum matrix as a reinforcement phase, which led to the formation of Al4 W compounds, W2 C carbides and Al4 C3 carbides within MMC. The presence of the needle-like Al4 C3 was detrimental to the mechanical properties of the MMC, due to its brittle nature. Through powder feeding with Ti and WC particles simultaneously during WPDL, laminated aluminum matrix compounds were produced under optimized parameter setup. XRD, SEM and TEM were employed to analyze microstructural features of the MMC. It was found that the formation of the brittle Al4 C3 carbide was inhibited in MMC due to the alloying effect of titanium. The various phases of MMC identified include Al, WC, W, TiAl3, TiAl, Ti3 Al and Al4 W. The microstructural features of the interface between the reinforcement phase of WC ceramic and the aluminum matrix were examined. Graphical abstract: Highlights: WCp /Al compound additive was manufactured by coincident wire-powder laser deposition. Titanium particle was fed with WC particles simultaneously into Al-melt. Brittle phase Al4 C3 was prohibited with new phase TiC and Al–Ti phase forming. Alloying effect of titanium on the microstructure was analyzed. In-situ reinforcement phase and foreign reinforcement existed in MMC together.